2023
DOI: 10.1111/faam.12365
|View full text |Cite
|
Sign up to set email alerts
|

Management accounting and control systems as devices for public value creation in higher education

Abstract: This paper investigates how management accounting and control systems (operationalized by using Simons’ levers of control framework) can be used as devices to support public value creation and as such it contributes to the literature on public value accounting. Using a mixed methods case study approach, including documentary analysis and semi‐structured interviews, we found diverging uses of control systems in the Dutch university of applied sciences we investigated. Although belief and interactive control sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 53 publications
(123 reference statements)
0
6
0
Order By: Relevance
“…In a similar vein, Grossi and Argento (2022) suggested that, beyond rationalizing NPM, research should focus more on the humanizing role of public sector accounting. Further pleas have been made in recent studies for researchers to embrace more public value-oriented perspectives when facilitating management accounting reforms (see, e.g., Salemans & Budding, 2023). This being said, our aim in this paper is not to focus on the reconceptualization of development, although our findings may suggest that the current climate is tipping in favor of challenging the existing conceptualization of market-led development and the associated public sector management accounting reforms in emerging economies.…”
Section: Development Npm and Emerging Economies: Contemporary Discussionmentioning
confidence: 91%
“…In a similar vein, Grossi and Argento (2022) suggested that, beyond rationalizing NPM, research should focus more on the humanizing role of public sector accounting. Further pleas have been made in recent studies for researchers to embrace more public value-oriented perspectives when facilitating management accounting reforms (see, e.g., Salemans & Budding, 2023). This being said, our aim in this paper is not to focus on the reconceptualization of development, although our findings may suggest that the current climate is tipping in favor of challenging the existing conceptualization of market-led development and the associated public sector management accounting reforms in emerging economies.…”
Section: Development Npm and Emerging Economies: Contemporary Discussionmentioning
confidence: 91%
“…For instance, (Bedford, 2015) identified a positive association between belief systems and workplace flexibility, while (Henri, 2006) examined the role of interactive control systems in fostering innovation. Furthermore, recent studies by (Phan et al, 2023), (Salemans & Budding, 2024), (Mura et al, 2021), Dávila( 2021), and(Müller-Stewens et al, 2020) have reinforced the relevance of the LoC framework in contemporary organizational contexts. (Martyn et al, 2016) underscored the adaptability of the LoC framework in addressing modern challenges such as corporate social responsibility (CSR), environmental accounting, and economic crises.…”
Section: Introductionmentioning
confidence: 92%
“…Second, Salemans and Budding (2024) integrated Public Value ideas with Simons’ (1995) levers of control to explore the role of management accounting and control systems in the creation of Public Value within Dutch universities of applied sciences. Based on a case study, the paper suggests that belief and interactive controls (respectively, concise, value‐laden, and inspirational control systems; and systems focusing on strategic items and data, as a driver for action) are actively used to implement new strategies formulated in terms of Public Value.…”
Section: The Emergence and Measurement Of Public Valuementioning
confidence: 99%
“…(2024), included in this Special Issue, the next section provides an overview of the changing focus on how universities have been managed over time. The following section discusses the emergence and measurement of Public Value themes in the university sector, particularly drawing on the considerations made in the work of Oppi and Galizzi (2024) and Salemans and Budding (2024) in this volume. The final section concludes by proposing a future research agenda for those interested in the study of the university sector and provides possible research questions to further this area.…”
Section: Introductionmentioning
confidence: 99%